Avaliação do desempenho de canal gramado na remoção de material suspenso em escoamento superficial pluvial - Moruzzi, Rodrigo Braga [UNESP]; Felipe, Mayara; Barbassa, Ademir Paceli; Sírio, Daniel De Lima Nascimento (FapUNIFESP (SciELO), 2017)
In this study, the performance of a natural channel in removing particulate matter from runoff was evaluate. For this purpose, different initial concentrations of particles, which were discharged by means of simulated 100 m in length and slope of 2% channel rains, were investigated. The measurements of particulate matter were made by means of total suspended solids (TSS) at different positions along the channel. Hydrograph and water levels in the canal during the passage of the flood wave were monitored. The removed fractions for each one of the isolated essays and also in a combined way were evaluated, by applying kriging interpolation. Removals around 50% were obtained for the channel position of 50 m and 70% for channel position of 80 m. The results indicated that the removal of particulate material is strongly dependent on the extension of the channel and the dynamic aspects arising from the passage of the flood wave influence in the process.
Performance of natural channel on removing suspended matter from runoff
Keywords: Diffuse pollution; Simulated rain; Urban drainage